A prospective observational study of prescription pattern of drugs used in the treatment of osteoarthritis in a tertiary care hospital - Patil, Lokesh V.; Nara, Manisha (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Treatment of Osteoarthritis aims at reducing pain and improving mobility. NSAIDS are commonly prescribed for symptomatic relief despite well documented adverse effects. Paracetamol with its better safety profile is recommended as the initial analgesic of choice. Osteoarthritis has significant socio-economic impact on the patients and not many studies are available to reflect upon the prescription pattern of drugs in Osteoarthritis. Hence, this study was chosen to generate important feedback to the clinician. The objectives of the study were to study the prescribing pattern of drugs used in the treatment of Osteoarthritis in Tertiary care hospital. Methods: Prescription for 300 osteoarthritis patients collected cross-sectional for 6 months from orthopedic out-patient department were analyzed. Results: 60% of females were affected. Average age of study was 56.46+/- 7.4 years. Knee joint (87.33%) was most commonly affected joint. Average number of drugs prescribed was 2.62 +/- 0.76. Out of 786 drugs prescribed 45.8% were NSAIDs. Paracetamol was underutilized. Conclusions: Paracetamol was underutilized while other NSAIDs were over prescribed.